PENGARUH KUALITAS PELAYANAN DAN MEDIA SOSIAL TERHADAP OMZET PENJUALAN PADA TOKO ROSE FLORIST BANDAR LAMPUNG - Loliyani, Rini; Bakti, Umar; Isabella, Astrid Aprica; Anisa, Nadia (Jurnal EBI, 2025)
This research aims to determine the influence of service quality and social media on sales turnover at the Rose Florist Shop in Bandar Lampung. The type of data in this research uses quantitative research. To determine the research sample, we used a probability sampling technique with the Slovin formula because the population was above 100 and obtained a result of 96.38 which was then rounded up to 96 respondents. The analysis techniques used are validity testing, reliability testing, classical assumption testing, and hypothesis testing. From the results of research that has been carried out, service quality and social media have a joint and significant influence on sales turnover at the Rose Florist shop in Bandar Lampung. Service quality and social media have an influence of 68.3% on sales turnover, and 31.7% is influenced by other factors not examined in this research.Key words: Service Quality, Social Media, Sales Turnover, Rose Florist, Lampung City